Zakat as a Tax Credit for Raising Indonesian Tax Revenue - Any Setianingrum; Aam Slamet Rusydiana; Penny Rahmah Fadhilah (International Journal of Zakat, 2019)
This study aims to select the most appropriate treatment of zakat and tax to maximize Indonesia taxation of the given three alternatives. The first alternative is zakat and taxes are not correlated. Second, zakat is used as deductions of taxable income. Third, zakat is used as a tax credit. The basic considerations for determining the rank of these three models are from the aspects of benefits, the costs, and the risks. The analytical tool used is ANP (Analytic Network Process). The research respondents are some experts and stakeholder of zakat and tax in Indonesia. Based on the result of this research, the first rank is zakat as a tax credit with a weight of 0,469. The second alternative is zakat as the deduction of Taxable Income with a weight of 0,385. The third or last alternative is zakat and tax has no direct relationship with the weight of 0,146. Based on this research, to increase tax revenue in Indonesia, zakat as a tax credit is advisable. Keywords: Zakat, tax, credit, ANP, Indonesia